Managing patients at risk for age-related macular degeneration: a Canadian strategy - Somani, Sohel; Hoskin-Mott, Ann; Mishra, Adit; Bois, Alain; Book, Brian H; Chute, Mark; Gaucher, Ronald; Winter, Barry (Canadian Journal of Optometry, 2019)
Background: To develop a consensus strategy for the management of patients at risk for age-related macular degeneration (AMD) for Canadian ophthalmologists, optometrists and physicians. Methods: Development of a consensus strategy began with a review of the literature and existing guidelines. A panel of retina specialists, ophthalmologists, and optometrists from across Canada assessed this evidence to distill what was learned and use this knowledge as the basis for developing a consensus strategy for managing patients at risk of AMD. Results: The expert panel has developed a series of recommendations for Canadian eyecare providers (eg. ophthalmologists, optometrists) and physicians to adopt as a preventive strategy for patients at risk of AMD. Interpretation: This consensus strategy is a practical guideline that can be adopted in the office setting to manage patients at risk of AMD and to advise patients with questions and concerns about AMD.